Self-Healing Alginate Hydrogel Formed by Dynamic Benzoxaborolate Chemistry Protects Retinal Pigment Epithelium Cells against Oxidative Damage - Minhua Liu; Yate Huang; Chunwen Tao; Weijia Yang; Junrong Chen; Li Zhu; Tonghe Pan; Ravin Narain; Kaihui Nan; Yangjun Chen (Gels, 2022)
Oxidative stress is considered as a major factor causing retinal pigment epithelium (RPE) dysfunction and finally leading to retinal diseases such as age-related macular degeneration (AMD). Developing hydrogels for RPE cell delivery, especially those with antioxidant feature, is emerging as a promising approach for AMD treatment. Herein, a readily prepared antioxidant alginate-based hydrogel was developed to serve as a cytoprotective agent for RPE cells against oxidative damage. Alg-BOB was synthesized via conjugation of benzoxaborole (BOB) to the polysaccharide backbone. Hydrogels were formed through self-crosslinking of Alg-BOB based on benzoxaborole-diol complexation. The resulting hydrogel showed porous micro-structure, pH dependent mechanical strength and excellent self-healing, remolding, and injectable properties. Moreover, the hydrogel exhibited excellent cytocompatibility and could efficiently scavenge reactive oxygen species (ROS) to achieve an enhanced viability of ARPE-19 cells under oxidative condition. Altogether, our study reveals that the antioxidant Alg-BOB hydrogel represents an eligible candidate for RPE delivery and AMD treatment.